Evidence against an Interaction between the mRNA Downstream Box and 16S rRNA in Translation Initiation - Moll, Isabella (American Society for Microbiology, 2001)
Based on the complementarity of the initial coding region (downstream box [db]) of several bacterial and phage mRNAs to bases 1469 to 1483 in helix 44 of 16S rRNA (anti-downstream box [adb]), it has been proposed that db-adb base pairing enhances translation in a way that is similar to that of the Shine-Dalgarno (SD)/anti-Shine-Dalgarno (aSD) interaction. Computer modeling of helix 44 on the 30S subunit shows that the topography of the 30S ribosome does not allow a simultaneous db-adb interaction and placement of the initiation codon in the ribosomal P site. Thus, the db-adb interaction cannot substitute for the SD-aSD interaction in translation initiation. We have always argued that any contribution of the db-adb interaction should be most apparent on mRNAs devoid of an SD sequence. Here, we show that 30S ribosomes do not bind to leaderless mRNA in the absence of initiator tRNA, even when the initial coding region shows a 15-nucleotide complementarity (optimal fit) with the putative adb. In addition, an optimized db did not affect the translational efficiency of a leaderless λ cI-lacZ reporter construct. Thus, the db-adb interaction can hardly serve as an initial recruitment signal for ribosomes. Moreover, we show that different leaderless mRNAs are translated in heterologous systems although the sequence of the putative adb's within helix 44 of the 30S subunits of the corresponding bacteria differ largely. Taken our data together with those of others (M. O'Connor, T. Asai, C. L. Squires, and A. E. Dahlberg, Proc. Natl. Acad. Sci. USA 96:8973–8978, 1999; A. La Teana, A. Brandi, M. O'Connor, S. Freddi, and C. L. Pon, RNA 6:1393–1402, 2000), we conclude that the db does not base pair with the adb.